Estimating the potential of skid incident at airport runway – a case study - Ng, Choy Peng; Faridah Hanim Khairuddin,; Wan Mohamed Syafuan Wan Mohamed Sabri,; Zawil Mohd Yusoff,; Yit, Hong Yee; Marzuki Ramli, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Skid resistance or friction on airport pavement plays an essential role in runway safety to ensure safe stopping distance. It also provides safety margins during take off and landing of aircraft especially in directional control by reducing the occurrence of overrun and veer-off incidents. The friction between pavement and tire is related to multiple factors such as pavement surface characteristics (microtexture and macrotexture), material intruded between tire and pavement surface (water, snow, and contaminants), tire conditions (types, wear, and inflation pressure), and vehicle operating conditions (vehicle speed and whether the wheel is rolling or locked). Skid incidents due to wet pavement surface at airport runway is a major concern especially in regions of wet-tropical climate countries such as Malaysia. Thus, this study was undertaken to measure the potential of skid incident at airport runway by collecting data on pavement surface characteristics. Field data collection on pavement surface microtexture was conducted using the British Pendulum Tester at a local airport runway to obtain data for the estimation of the skid number (SN). Due to constraints, pavement surface macrotexture test was unable to be conducted at site. However, the pavement surface macrotexture was able to be estimated based on previous research. The potential of the skid incident was estimated by calculating the SN using the aircraft’s touch down speed at the airport runway, varies from 50 to 70 knots (57.5 – 80.6 mph or 92.6 – 129.6 km/h). The results of the estimation indicated that the possibility of the skid incident occurrence was high. This study provides useful insights for airport authority to investigate the potential of overrun and veer-off incidents of aircraft at the airport runway.